Effect of high levels of suplemental zinc on piglets performance and mortality - Bertol, Teresinha Marisa; Brito, Benito Guimarães de (Pesquisa Agropecuaria Brasileira, 1998)
The present study aim was to evaluate high levels of Zn from ZnO in the weaning diets of piglets. It were compared two different levels of zinc (0 and 3,000 ppm) from 0 to 21 days after weaning, three different levels (0, 1,500 and 3,000 ppm) from 22 to 42 days after weaning, and four level combinations 0/0, 3,000/0, 3,000/1,500 and 3,000/3,000 ppm. One hundred and eighty six crossbred (D x LW) weaned piglets (28±2 days of age) were used. The supplementation with 3,000 ppm Zn up to 21 days of experiment increased the average daily gain (GPMD, P
Keywords: edema disease; pig nutrition; zinc oxide; piglet weaning